Вплив температури на адгезійні властивості рециклінгових пластичних мастил - Григоров, Андрій Борисович (ДП "УХІН", 2020)
Представлені результати дослідження впливу температури на адгезійні властивості рециклінгових пластичних мастил. Для визначення даного показника застосовували лабораторну центрифугу з робочою ємністю, що обігрівається. Дослідженню піддавали спеціально отримані рециклінгові пластичні мастила. Як дисперсійне середовище в цих пластичних мастилах виступали відпрацьовані гідравлічна олива HLP-46, моторна олива SAE 15W-40 API SL / CI-4 і трансмісійна олива SAE 85W-90 GL-5. З цих олив шляхом відстоювання та центрифугування попередньо вилучались вода і механічні домішки, які є енергетичним баластом у виробництві, ускладнюють технологічний процес і негативно впливають на якість кінцевого продукту. Як загущувач в оливу вводили 5% (мас.) поліетилену низького тиску. Наведено опис методики приготування системи «олива - загущувач». Отримані зразки наносили на знежирені сталеві пластини шаром товщиною 0,1 мм. Ці пластини вміщували в центрифугу. Адгезійні властивості визначали за залишковою масою мастила на пластині після випробування. За результатами запропоновано розділити режим експлуатації вузла з пластичним мастилом на оптимальний, тобто штатний, і екстремальний, котрий може в кінцевому підсумку призвести до мастильного голодування поверхонь тертя у вузлі агрегату. Перехідним значенням між цими режимами на підставі практичних рекомендацій фірм-виробників підшипників різних типів можна вважати зменшення початкової кількості пластичного мастила в вузлі до 50 %. Залежно від функціонального призначення відпрацьованої оливи, котра виступає базою для пластичного мастила, підвищення температури проби на кожен 1 °С в середньому знижує швидкість обертання проби до досягнення граничного значення, на 5,6 ÷ 14,4 об/хв. Результати досліджень показали: для використання в якості базового компонента рециклінгових пластичних олив для досягнення високих адгезійних властивостей кінцевого продукту необхідно використовувати трансмісійні та моторні оливи.

It is shown that without studying the effect of temperature on the adhesive properties of recycling greases, the principle of both preparation and composition of which are described in the author’s previous works, the practical application of these materials is impossible. This indicator is esp ecially important for determining the interval of operating temperatures of oil in the nodes of the units for various purposes. The results of a study of the effect of temperature on the adhesive properties of recycling greases are presented. To determine this indicator, a laboratory centrifuge with a heated working capacity was used. The study was subjected to specially obtained recycling greases. The used HLP-46 hydraulic oil, SAE 15W-40 API SL / CI-4 engine oil and SAE 85W-90 GL-5 transmission oil were the dispersion medium in these plastic lubricating oils. From these oils, by settling and centrifuging, water and mechanical impurities, which are the energy ballast in the production, were previously removed, complicate the process and adversely affect the quality of the final product. As a thic kener, 5% (mass.) of low-pressure polyethylene was introduced into the oils. The description of the methodology for the preparation of the oil-thickener system is given. The obtained samples were applied to defatted steel plates with a layer thickness of 0.1 mm. These plates were placed in a centrifuge. Adhesive properties were determined by the residual mass of oil on the plate after the test. According to the results, it is proposed to divide the operating mode of the unit with grease into optimal, that is, regular, and extreme, which can ultimately lead to the lubrication starvation of friction surfaces in the unit assembly. A transition value between these modes on the basis of pra ctical recommendations of manufacturers of bearings of various types can be considered a d ecrease in the initial quantity of grease in the assembly to 50%. Depending on the functional purpose of the used oil, which acts as the basis for grease lubrication, increasing the temperature of the sample for every 1 ° C on average reduces the speed of rotation of the sample until the thres hold value is reached, by 5.6 ÷ 14.4 rpm. The research results showed: for use as a basic component of recycled greases to achieve high adhesive properties of the final product, it is necessary to use transmission and motor oils.
Effect of temperature on adhesive properties of recycling plastic lubricants
Keywords: хімічна промисловість; граничні значення; фактори швидкості; базові оливи; grease; base oil; adhesive properties; ultimate value; quality indicator; speed factor; temperature